Psicopedagogia e práticas inovadoras de algumas professoras dos anos iniciais do ensino fundamental - Santos, Janaina Goncalves dos [UNIFESP] (2015)
This study aims to identify the contributions from Psychopedagogy in the constitution of teaching knowledge and adopting innovative practices. The Psychopedagogy field studies learning processes and possible causes of difficulties in learning. With structured contributions from different fields of knowledge, in Psychopedagogy, there is the possibility of a more informed understanding about human development, as well as the need to enhance the mechanisms of acquiring knowledge at school. As a theoretical basis, we seek authors who have studies on Pedagogical Innovation: Garcia (1980), Huberman (1986); Teaching Training: Pimenta (1999, 2002, 2004), Nóvoa (1995), Libâneo (1999, 2004), Candau (1996), Gatti (2010) Imbernón (2009) and Psychopedagogy: Bossa (2000, 2001), Masini (1993, 1999), aiming to understand the contributions of training in Psychopedagogy for the teaching how to do. Empirical data were obtained through interviews with teachers trained in Psychopedagogy, who work in the early years of Elementary School. By analyzing the reports of the interviews, it was found that the psycho-pedagogical knowledge serves as support for the teachers? how to do, with improvements in the daily practice of teachers in the classroom and therefore, ensuring better students? learning. The continuing education of the respondents in the field of Psychopedagogy highlighted the contribution of this area in the creation and improvement of teaching knowledge regarding to didactic-pedagogical knowledge.